Reproductive capacity of Pseudotsuga menziesii (Mirb.) Franco in Christmas tree plantations - Ramírez-Martínez, Garilizbeth; Muñoz-Gutiérrez, Liliana; Vargas-Hernández, J. Jesús (Ecosistemas y Recursos Agropecuarios, 2025)
Pseudotsuga menziesii is a conifer subject to special protection,its populations are small and discontinuous,with isolated individuals and commonly dominated by other species; the areas are considered of high genetic value for conservation; economically important conifer in Mexico,due to the high demand it has as a Christmas tree due to its color, aroma and retention capacity of the foliage. For the establishment of commercial plantations, a continuous supply of germplasm in quantity and quality must be guaranteed. The objective was to determine the reproductive characteristics of cones and seeds of juvenile trees of P. menziesii from floral induction trials in Christmas tree plantations established in Acoculco, Chignahuapan, Puebla. Mature cone samples were taken from trees, that were treated with AG4/7 with the ringing of the trunk, of which two groups were formed with different numbers of cone samples, one group received pollen and the other did not. The data was analyzed with the UNIVARIATE and GLM procedures in SAS and a comparison test of means with Tukey (p≤0.05). The application of AG4/7, in combination with the ringing of the trunk turn out to be effective treatments for the formation of male and female reproductive structure, it induced a greater number of full seeds and greater seed efficiency (1.54 and 2.94%). The artificial pollinations to increase the proportion of full seeds. It is recommended to apply AG4/7 to induce early flowering, increase the production of cones and assist with pollination to increase the number of seeds and reduce the rate of inbreeding.
Keywords: gibberellic acid; full seeds; inbreeding; pollination; seed efficiency